2018
DOI: 10.1371/journal.pone.0194515
|View full text |Cite
|
Sign up to set email alerts
|

Empathizing-systemizing cognitive styles: Effects of sex and academic degree

Abstract: This study tests if the drives to empathize (E) and systemize (S), measured by the Systemizing Quotient-Revised (SQ-R) and Empathy Quotient (EQ), show effects of sex and academic degree. The responses of 419 students from the Humanities and the Physical Sciences were analyzed in terms of the E-S theory predictions. Results confirm that there is an interaction between sex, degree and the drive to empathize relative to systemize. Female students in the Humanities on average had a stronger drive to empathize than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
4
20
0
4
Order By: Relevance
“…The male students in Exact Sciences were more systemizing than the female students in Human Sciences, and overall, regardless of sex, the science students had higher levels of systemizing than empathizing characteristics, while the opposite was true for the humanities students. 29,30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The male students in Exact Sciences were more systemizing than the female students in Human Sciences, and overall, regardless of sex, the science students had higher levels of systemizing than empathizing characteristics, while the opposite was true for the humanities students. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…The male students in Exact Sciences were more systemizing than the female students in Human Sciences, and overall, regardless of sex, the science students had higher levels of systemizing than empathizing characteristics, while the opposite was true for the humanities students. 29,30 But regardless of gender, the importance of the professionals' sensitivity, especially in the health area, in care for the person under their care is indisputable. Literature analyses point to the existence of two professional groups in terms of empathetic profile.…”
Section: Scalesmentioning
confidence: 99%
“…In a similar vein, West et al (2008) reported that an individual's need for cognition and openmindedness predicted their critical thinking abilities. Several studies have reported that the 'systemizing' cognitive style, which drives to analyze the rules underlying a system, is related to interest in science and engineering (Billington et al, 2007;Kidron et al, 2018). Some contemporary work in science communication has also sought to predict science information engagement on the basis of individual traits.…”
Section: Non-cognitive Explanations Of Interest and Engagement With Smentioning
confidence: 99%
“…Cognitive styles are frameworks for the way people think, gather, process, use, and remember information (Kozhevnikov 2007). E-S theory (see e.g., Baron-Cohen et al 2003;Wheelwright et al 2006;Kidron et al 2018;Svedholm-Häkkinen et al 2016) deals specifically with autism's social and non-social features, attributing the social difficulties characteristic of the condition to weaknesses in cognitive empathizing-the ability and drive to imagine another person's mental states (i.e., their thoughts, intentions, desires, feelings)-and the autistic tendency for detailorientation to strengths in systemizing. It further predicts that women will be stronger empathizers than men, who are said to possess a cognitive style rooted in systemizing.…”
Section: Systemizingmentioning
confidence: 99%